Volume 7: Ocean Space Utilization; Professor Emeritus J. Randolph Paulling Honoring Symposium on Ocean Technology 2014
DOI: 10.1115/omae2014-23818
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of the Flow Features Around Heave Plates Oscillating Close to a Free Surface or Seabed

Abstract: Performance of heave plates used in offshore structures is strongly influenced by their added mass and damping, which are affected by proximity to a boundary. A previous paper by the authors presented numerical simulations of the flow around a circular solid disk oscillating at varying elevations from seabed [1]. The force calculated was used to evaluate the added mass and damping coefficients for the disk. The simulations suggest that as the structure moves closer to the seabed the added mass and damping coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…It would be interesting to investigate in detail, using the CFD, the dissipation mechanisms. Such an attempt is being pursued in a recent reference [12,45].…”
Section: Added Mass and Dampingmentioning
confidence: 98%
“…It would be interesting to investigate in detail, using the CFD, the dissipation mechanisms. Such an attempt is being pursued in a recent reference [12,45].…”
Section: Added Mass and Dampingmentioning
confidence: 98%
“…This reduces risks and helps to optimize the design of the prototype platform. Hydrodynamic data on heave plates are usually reported using two non-dimensional characteristic parameters (Keulegan-Carpenter number KC and frequency parameter β) that represent the amplitude and frequency of oscillation of any heave plate configuration [6][7][8][9][10]. These dimensionless parameters of relevance are defined as [11]:…”
Section: Introductionmentioning
confidence: 99%
“…When a heave plate is brought closer to a surface either by increasing the KC value or by reducing the draft of the attached column, then some changes become apparent. Numerical studies by [10] have shown that vortices shed by heave plates when executing large amplitude oscillations can disturb an otherwise quiescent free surface. They also showed that both coefficients exhibited dramatic variations with increasing KC, which depended on the distance from the free surface.…”
mentioning
confidence: 99%
“…Although the true velocity field around a heave plate is rotational, the theoretical added mass does provide a reference against which the actual added mass can be normalized. This method of normalization has been used by several authors including Lake et al [6], Garrido-Mendoza et al [14], and Tao and Dray [15].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is often mentioned in the heave plate literature for oil and natural gas, β is not typically used as an independent parameter. Rather, all tests are conducted at a set β to reduce the effect of frequency dependence in added mass [7], [14].…”
Section: Introductionmentioning
confidence: 99%